Recent influenza activity in tropical Puerto Rico has become synchronized with mainland US. Issue 5 (2nd July 2020) - Paz–Bailey, Gabriela; Quandelacy, Talia M.; Adams, Laura E.; Olsen, Sonja J.; Blanton, Lenee; Munoz-Jordan, Jorge L.; Lozier, Matthew; Alvarado, Luisa I.; Johansson, Michael A.
Abstract: Background: We used data from the Sentinel Enhanced Dengue Surveillance System (SEDSS) to describe influenza trends in southern Puerto Rico during 2012‐2018 and compare them to trends in the United States. Methods: Patients with fever onset ≤ 7 days presenting were enrolled. Nasal/oropharyngeal swabs were tested for influenza A and B viruses by PCR. Virologic data were obtained from the US World Health Organization (WHO) Collaborating Laboratories System and the National Respiratory and Enteric Virus Surveillance System (NREVSS). We compared influenza A and B infections identified from SEDSS and WHO/NREVSS laboratories reported by US Department of Health and Human Services (HHS) region using time series decomposition methods, and analysed coherence of climate and influenza trends by region. Results: Among 23, 124 participants, 9% were positive for influenza A and 5% for influenza B. Influenza A and B viruses were identified year‐round, with no clear seasonal patterns from 2012 to 2015 and peaks in December‐January in 2016‐2017 and 2017‐2018 seasons. Influenza seasons in HHS regions were relatively synchronized in recent years with the seasons in Puerto Rico. We observed high coherence between absolute humidity and influenza A and B virus in HHS regions. In Puerto Rico, coherence was much lower in the early years but increased to similar levels to HHS regions by 2017‐2018. Conclusions: Influenza seasons in Puerto Rico have recently become synchronized with seasons in US HHS regions. Current US recommendations are for everyone 6 months and older to receive influenza vaccination by the end of October seem appropriate for Puerto Rico.